A serviço da ciência: a fotografia como instrumento da pesquisa científica na expedição Thayer (1865 – 1866) - Miranda, Clarissa Franco de (2017)
The present work proposes to understand photography as a tool for scientific research, reflecting from the performance of Thayer Expedition, a North American commission led by the naturalist Louis Agassiz, who came to Brazil between 1865 and 1866. Between the XVIII and XIX centuries, the so-called scientific expeditions, attached to the cosmopolitan sense of European imperialism, spread throughout the world, following a systematic studies pattern and research, naturalists targeted to analyze and classify the places visited, their nature, their culture and their natives. Several scientists came to Brazil bringing with them apprentices, specialists, curious, and one other professional, the photographer, this one now indispensable in clearing and gathering data of the expeditions. The naturalists brought the photograph to their research as part of the empiricist method, considered the reflection of reality printed on paper, it would come to give science greater reliability and proof. Amidst the discussions of a creationist Natural Philosophy and the principles of evolutionary theory, the production of photographic images became a field of disputes inside the science. The records from these experiences, relationships, and strangeness (photographs, travel reports, and scientific literature) make up the most considerable source for the dissertation. Analyzing the conflicts that surrounded different scientific theories, from the imperial intervention to the racialism, and its attempts of verification, the objective is to understand the production of photographic images in the service of science and the techniques appropriations by the empiricist method, understanding how Brazil was inserted in the scientific debate and how the naturalists used the local case records to compose an understanding of universal science.